2019
DOI: 10.1111/cas.13993
|View full text |Cite
|
Sign up to set email alerts
|

Targeting HOX/PBX dimer formation as a potential therapeutic option in esophageal squamous cell carcinoma

Abstract: Homeobox genes are known to be classic examples of the intimate relationship between embryogenesis and tumorigenesis, which are a family of transcriptional factors involved in determining cell identity during early development, and also dysregulated in many malignancies. Previously, HOXB7 , HOXC6 and HOXC8 were found abnormally upregulated in esophageal squamous cell carcinoma (ESCC) tissues compared with normal mucosa and seen as poor progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 36 publications
0
22
0
Order By: Relevance
“…Regarding the safety of the peptide HXR9, we found that it was not cytotoxic to the nonmalignant esophagus epithelial cell line HEEC and bodyweight loss in mice treated with HXR9 was not significantly greater than the control. 28 Meanwhile, the combination of HXR9 with cisplatin did not lead to significant weight loss in mice. In addition, previous studies have indicated that there is a rapid accumulation of HXR9 in the first few hours and it then remains stable beyond 24 hours and local delivery of HXR9 into tumors in mice has not resulted in a local inflammatory response.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Regarding the safety of the peptide HXR9, we found that it was not cytotoxic to the nonmalignant esophagus epithelial cell line HEEC and bodyweight loss in mice treated with HXR9 was not significantly greater than the control. 28 Meanwhile, the combination of HXR9 with cisplatin did not lead to significant weight loss in mice. In addition, previous studies have indicated that there is a rapid accumulation of HXR9 in the first few hours and it then remains stable beyond 24 hours and local delivery of HXR9 into tumors in mice has not resulted in a local inflammatory response.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it was found that disruption of HOXB7/PBX by HXR9 caused transcription alteration of genes such as MPL, IL-15, IL-23A and IL-24, which encode cytokines involved in regulating the activation of JAK-STAT signaling pathway or induction of apoptosis in our previous study. 28 It suggested that HXR9 may disrupt HOX/PBX functions through modifying cyctokine-JAK-STAT pathway activation to sensitize ESCC cells to cisplatin. However, the underlying exact mechanism is to be investigated in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such interaction shuts down the expression of various genes involved in apoptosis [8,237,238]. Disruption of HOX/PBX interaction impacts cell proliferation and restores cell death in various solid tumor cell models [238], including melanoma [236,239], renal cell carcinoma [240], ovarian cancer (such as the SK-OV3 cell model or primary samples [241,242]), breast cancer [243], prostate cancer [244], asbestos-associated mesothelioma [245], and oral and esophageal squamous cell carcinoma [246,247]. HXR9 was also evaluated in AMLs based on the relevance of HOXA9 and PBX3 interaction in AML [29,75,248,249], but other expressed HOX/PBX3 interfaces may also be disrupted by HXR9 in AML.…”
Section: Direct Targeting Of Hoxa9mentioning
confidence: 99%
“…Cancer cells' sensitivity to this peptide is highly correlated to their HOX expression profile, albeit the subset of HOX genes which act as oncosuppressors is not affected [34]. This peptide has shown to be effective in oesophageal and oral squamous cell carcinomas [36,37], melanoma [35,38], ovarian cancer (OC) [39], breast cancer [40], meningioma [41], prostate cancer [42], and leukaemia [43]. The use of RNA interference mechanisms [44,45] and the control of HOX methylation status [46] are additional tools that can control HOX expression with therapeutic function.…”
Section: Hox Genes and Cancermentioning
confidence: 98%